Fluorine and nitrogen doping of zinc oxide to enhance dielectric storage of PVDF based particulate composites - Chen, Shuyang; Thakur, Vijay Kumar; Skordos, Alexandros A. (Elsevier, 2024)
Polyvinylidene fluoride (PVDF) based polymer nanocomposites with ceramics as nanofiller have been investigated as a solution for energy storage devices due to their unique and attractive combination of processability and electrical properties. This work assesses two dopants (fluorine and nitrogen) for zinc oxide (ZnO) nanoparticles PVDF matrix composites as a means of improving dielectric properties targeting capacitive storage. Fluorine doping achieves improved performance compared to pure ZnO nanocomposites increasing the decomposition temperature by 15 °C to 463 °C with 15 wt% F-doped ZnO and reducing the weight loss by 4.2 %. The highest dielectric constant that can be achieved with the addition of fluorine is about 70 at room temperature, which is more than 3 times greater than that of pure ZnO nanocomposite. Nitrogen doping also enhances the permittivity of the nanocomposites at ambient temperature but limit enhancement at high temperature due to the lower activation energy.
Keywords: Polymer-ceramic particle composites; Dielectric spectroscopy; Relaxation; Dielectric storage; Thermal analysis